Detection of a westward hotspot offset in the atmosphere of hot gas giant CoRoT-2b. (March 2018) - Dang, Lisa; Cowan, Nicolas; Schwartz, Joel; Rauscher, Emily; Zhang, Michael; Knutson, Heather A.; Line, Michael; Dobbs-Dixon, Ian; Deming, Drake; Sundararajan, Sudarsan; Fortney, Jonathan; Zhao, Ming
Abstract Short-period planets exhibit day–night temperature contrasts of hundreds to thousands of kelvin. They also exhibit eastward hotspot offsets whereby the hottest region on the planet is east of the substellar point1 ; this has been widely interpreted as advection of heat due to eastward winds2 . We present thermal phase observations of the hot Jupiter CoRoT-2b obtained with the Infrared Array Camera (IRAC) on the Spitzer Space Telescope. These measurements show the most robust detection to date of a westward hotspot offset of 23 ± 4°, in contrast with the nine other planets with equivalent measurements3–10 . The peculiar infrared flux map of CoRoT-2b may result from westward winds due to non-synchronous rotation11 or magnetic effects12, 13, or partial cloud coverage, that obscure the emergent flux from the planet's eastern hemisphere14–17 . Non-synchronous rotation and magnetic effects may also explain the planet's anomalously large radius12, 18 . On the other hand, partial cloud coverage could explain the featureless dayside emission spectrum of the planet19, 20 . If CoRoT-2b is not tidally locked, then it means that our understanding of star–planet tidal interaction is incomplete. If the westward offset is due to magnetic effects, our result represents an opportunity to study an exoplanet's magnetic field. If it has eastern clouds, then it means that a greater understanding of large-scale circulation on tidally locked planets is required. Global circulation theory predicts strong equatorial jets at the equators of hot gas giant exoplanets that blow hot gas to the east, resulting in an eastward hotspot. Here, Dang et al. present a detection of a hotspot significantly offset to the west.